Capital Structure Analysis Of Pharmaceutical Companies Listed On The Indonesian Stock Exchange - Roswinna, Winna; Lusiana Yulianti, Maria; Suryaman, Suryaman; Zakaria, Mohammad; Maulana, Hendri (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
For many companies, the capital structure is an important part of the company. every company competes to innovate products, market expansion, quality human resources, this is done in order to increase the value of the company and get the maximum possible profit. The capital structure has an important goal, namely to maximize the value of the company and minimize the overall cost of capital. This study aims to examine the influence of profitability and liquidity on the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange through the company's financial statements, namely in the period from 2012 to 2021. The type of research used in this research is case study research with a quantitative approach and the data source used is secondary data. The processed data consists of data on debt, assets, equity and profits in the annual financial reports (Annual Report) of Pharmaceutical Companies Listed on the Indonesia Stock Exchange. The calculation technique used in this research is using the panel fund regression approach through the help of eviews 10. The results show that profitability and liquidity have a significant effect on capital structure individually, meaning that profitability and liquidity can affect capital structure.